Resolusi Konflik Melalui Model Pengampunan Vita Activa Arendt Dalam Komunikasi Generasi Muda Kalimantan Barat - Joshua Fernando; Rustono Farady Marta (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
The life of a cultural society cannot be avoided by potential conflicts that arise at any time. West Kalimantan has a history of inter-ethnic conflict, which is currently still undergoing a recovery phase. The young generation is the subject that encourages harmony in West Kalimantan. This study aims to find a model of the forgiveness process of past ethnic conflicts that occur in the young generation of West Kalimantan. This study was examined using a qualitative method through an explorative phenomenological study with the phenomenological perspective of forgiveness Hannah Arendt. The results of this study indicate that the collective relationships built by the younger generation and the occurrence of cultural acculturation help in the process of natural forgiveness. On the other hand, forgiveness is not fully realized due to the occurrence of collections of collective memory such as stereotypes, past stories, and exposure to charged media content about past ethnic conflicts in the young generation of West Kalimantan. The substance of this study is in the form of policy recommendations on the role of the community, traditional leaders, and regional governments collaborating to achieve just and prosperous reconciliation in West Kalimantan.